Can work make you mentally ill? A systematic meta-review of work-related risk factors for common mental health problems. Issue 4 (20th January 2017) - Harvey, Samuel B; Modini, Matthew; Joyce, Sadhbh; Milligan-Saville, Josie S; Tan, Leona; Mykletun, Arnstein; Bryant, Richard A; Christensen, Helen; Mitchell, Philip B
Abstract : It has been suggested that certain types of work may increase the risk of common mental disorders, but the exact nature of the relationship has been contentious. The aim of this paper is to conduct the first comprehensive systematic meta-review of the evidence linking work to the development of common mental health problems, specifically depression, anxiety and/or work-related stress and to consider how the risk factors identified may relate to each other. MEDLINE, PsychInfo, Embase, the Cochrane Collaboration and grey literature databases were systematically searched for review articles that examined work-based risk factors for common mental health problems. All included reviews were subjected to a quality appraisal. 37 review studies were identified, of which 7 were at least moderate quality. 3 broad categories of work-related factors were identified to explain how work may contribute to the development of depression and/or anxiety: imbalanced job design, occupational uncertainty and lack of value and respect in the workplace. Within these broad categories, there was moderate level evidence from multiple prospective studies that high job demands, low job control, high effort–reward imbalance, low relational justice, low procedural justice, role stress, bullying and low social support in the workplace are associated with a greater risk of developing common mental health problems. While methodological limitations continue to preclude more definitive statements on causation between work and mental disorders, there is now a range of promising targets for individual and organisational-level interventions aimed at minimising mental health problems in the workplace.